Assessing the accuracy of English-as-a-second-language eyewitness testimonies and contemporaneous officer notes using two methods - Allison, Meredith (Applied psychology in criminal justice, 2017)
Although English-as-a-Second Language (ESL) eyewitnesses interact regularly with police officers in the US and Canada, little research has examined their testimonies. This study sought to assess the testimony accuracy of 17 ESL witnesses, and the contemporaneous notes the officers made during free and cued recall questioning. We assessed accuracy using two methods: A checklist approach (CL) that has been used in past studies (e.g., List, 1986) and an inductive microanalysis of face-to-face dialogue (MFD) approach that was developed for this study. We found that witnesses gave more accurate information in free recall and made more errors in cued recall when both the CL and MFD methods of analysis were used. The same pattern of results held for the officer note data. When we directly compared the MFD and CL data, however, we found that the MFD method captured more information (both accurate and inaccurate witness details), suggesting that it provides richer accuracy data for eyewitness testimony and officer notes. Future research on ESL witness testimony using the MFD approach is discussed.